Enhancement of the Tumor Suppression Effect of High-dose Radiation by Low-dose Pre-radiation Through Inhibition of DNA Damage Repair and Increased Pyroptosis - Xinfeng Wei; Junxuan Yi; Citong Zhang; Mingwei Wang; Rui Wang; Weiqiang Xu; Mingqi Zhao; Mengdie Zhao; Teng Yang; Wei Wei; Shunzi Jin; Hui Gao (SAGE Publishing, 2024)
Radiation therapy has been a critical and effective treatment for cancer. However, not all cells are destroyed by radiation due to the presence of tumor cell radioresistance. In the current study, we investigated the effect of low-dose radiation (LDR) on the tumor suppressive effect of high-dose radiation (HDR) and its mechanism from the perspective of tumor cell death mode and DNA damage repair, aiming to provide a foundation for improving the efficacy of clinical tumor radiotherapy. We found that LDR pre-irradiation strengthened the HDR-inhibited A549 cell proliferation, HDR-induced apoptosis, and G2 phase cell cycle arrest under co-culture conditions. RNA-sequencing showed that differentially expressed genes after irradiation contained pyroptosis-related genes and DNA damage repair related genes. By detecting pyroptosis-related proteins, we found that LDR could enhance HDR-induced pyroptosis. Furthermore, under co-culture conditions, LDR pre-irradiation enhances the HDR-induced DNA damage and further suppresses the DNA damage-repairing process, which eventually leads to cell death. Lastly, we established a tumor-bearing mouse model and further demonstrated that LDR local pre-irradiation could enhance the cancer suppressive effect of HDR. To summarize, our study proved that LDR pre-irradiation enhances the tumor-killing function of HDR when cancer cells and immune cells were coexisting.